Sociodemographic and Histological Trends of Breast Lumps in A Sub-Saharan African Population: A Cross-Sectional Study in A Surgical Oncology Department - Mbessoh Kengne, Ulrich Igor; Abou Talib Thiam, Jaafar Ibn; Balde, Salif; Ndiaye, Mamadou; Fall, Amacoumba; Kasokota, Esaie; Niasse, Awa; Amadi Sow, Amadou; Sow, Mamadou; Ezzet Charfi, Mohammed; Ka, Sidy (Clinical Medicine And Health Research Journal, 2023)
Objective: The purpose of the study was to present histological profile of both benign breast tumors (BBT) and breast cancer (BC) in our setting and highlight age trends in the occurrence of BBT. Methods: A retrospective cross-sectional study was conducted in the surgical oncology unit of the Dalal Jamm University Hospital from January to July 2023. Dalal Jamm University Hospital is a teaching hospital based in Dakar, Senegal. Results: The median age was 45 years for BC and 31.5 years for BBT. The main histological types of BC were invasive ductal carcinoma (93.2%) and invasive lobular carcinoma (4.5%) whereas it was fibroadenoma (66.6%) for BBT. Fibroadenoma and benign phyllodes tumor was more common in adolescents and under 40 years (p = 0.046) old while fibrocystic changes were more prevalent during perimenopause (p < 0.001). Conclusion: Invasive ductal carcinoma and fibroadenoma are the most common breast tumors in sub-Saharan African setting. Fibroadenoma and benign phyllodes tumor are more prevalent in adolescents and under 40 years while fibrocystic changes occur most within the fourth and fifth decades of life.